High Cycle Fatigue Life Prediction of Single-Crystal Specimen Based on TCD Method and Crystal Plasticity Theory. (19th January 2023) - Wu, Yunwu; Liu, Yixiong; Wang, Wei; Li, Ying; Geng, Rui
Abstract : This paper performs a comprehensive investigation on the high cycle fatigue (HCF) life prediction of turbine blade with film cooling holes. The modified theory of critical distance (MTCD) method is proposed to estimate the fatigue life of the specimen considering the notch sensitivity coefficient and multiaxial stress effect. Then, two types of specimens were designed with regard to the single-hole and multihole conditions. Afterwards, the dangerous path and fatigue life of the two specimens were achieved implementing the MTCD method. Then, the experiments and failure analysis were carried out. The results show that the stress concentration and multiaxial stress resulting from the film cooling holes are the primary reasons that the cracks originated. Meanwhile, the dangerous path of the single-hole specimen is quite different from the multihole specimen due to the interhole interference. Finally, most of the calculated fatigue life is within the twice error band of the tested life.